PENGARUH STRES KERJA, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN: THE EFFECT OF JOB STRESS, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE TURNOVER INTENTION - Annisa Widyawati; Roni Faslah; Christian Wiradendi Wolor (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This study aims to determine the effect of job stress, job satisfaction, and organizational commitment (Y) on employee’s turnover intention. Using a non-probability sampling method using a purposive sampling technique. The sample used in this study was 111 respondents with the criteria of PT X permanent employees who work in the production, marketing and external divisions. The data analysis technique in this study uses Multiple Linear Regression with IBM SPSS 26. The results of this study indicate that job stress has a positive and significant effect on turnover intention, job satisfaction has a negative and significant effect on turnover intention, organizational commitment has a negative and significant effect on turnover intention, and there is an influence between job stress, job satisfaction, and organizational commitment on turnover intention